Value-Added Model (VAM) Research for Educational Policy: Framing the Issue. - Audrey Amrein-Beardsley; Clarin Collins; Sarah A. Polasky; Edward F. Sloat (Arizona State University, 2013)
In this manuscript, the guest editors of the EPAA Special Issue on "Value-Added Model (VAM) Research for Educational Policy" (1) introduce the background and policy context surrounding the increased use of VAMs for teacher evaluation and accountability purposes across the United States; (2) summarize the five research papers and one research-based commentary that were peer-reviewed and selected for inclusion in this special issue; and (3) discuss the relevance of the papers both individually and collectively. Their importance is discussed in terms of each paper's contribution to the general research on this topic and each paper's potential to inform educational policy. In addition, the papers reflect our shared thinking about VAMs, VAM output, and the inference-based decisions for which VAMs are increasingly being used.